Stress cardiomyopathy misinterpreted as ST-segment elevation myocardial infarction in a patient with aneurysmal subarachnoid hemorrhage: a case report - Enache Iulian; Radu Răzvan Alexandru; Terecoasă Elena Oana; Dorobăţ Bogdan; Tiu Cristina (Sciendo, 2020)
Cardiac abnormalities are frequently reported in acute subarachnoid hemorrhage (SAH) patients. However, frank ST-elevation and myocardial dysfunction mimicking acute coronary syndrome is a rare occurrence. Systemic and local catecholamine release mediate myocardial injury and may explain raised troponin levels, concordant regional wall motion abnormalities and systolic dysfunction. These findings can pose a significant problem in the acute setting where "time-is-muscle" paradigm can rush clinicians towards a "rule-in" diagnosis of acute myocardial infarction.